Minimal residual disease detection for acute lymphoblastic leukaemia in peripheral blood-Are we there yet? - Trka, Jan; Fronkova, Eva (British journal of haematology, 2025)
Can peripheral blood be used to detect residual disease in acute lymphoblastic leukaemia (ALL) when we increase the sensitivity of the method used? Bendig et al. found that a larger amount of material and the use of next-generation sequencing (NGS) detects MRD in peripheral blood in up to half of patients with B-cell precursor ALL (BCP-ALL) where routine examination was negative. However, a negative result does not exclude the presence of residual disease and thus still limits the use of peripheral blood. Commentary on: Bendig et al. Next-generation sequencing and high DNA input identify previously missed measurable residual disease in peripheral blood of B-cell precursor acute lymphoblastic leukaemia. Br J Haematol 2025; 206:353-356.
Keywords: vysoce účinné nukleotidové sekvenování; akutní lymfatická leukemie; Neoplasm, Residual; reziduální nádor; peripheral blood; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; ALL; High-Throughput Nucleotide Sequencing; residual disease; lidé